Systematic review of instruments for assessing social support network for elderly people - Domingues, Marisa Accioly (2013)
It is essential to examine the social support through the perspective of the individual to be able to identify the composition, function and quality of each social support network. For both, there are instruments that enable this understanding. Within this context, the objective of a brief description of the types of validation of instruments and examine some questionnaires, scales and charts that can be useful when assessing the social support of elderly persons and which are widely used in Brazil and abroad. Methods. We conducted through literature search strategy based on the terms: "instruments of social networks", "instruments of social support”, “elderly and social relations”. And their equivalents in Portuguese to search in LILACS. The abstracts of retrieved articles were reviewed to verify compliance with the criteria of inclusion and exclusion. The assessment of social relations is increasingly necessary for comprehensive care to the elderly. Family support, the first source of care for the elderly, is declining sharply, which puts us face a great challenge: to encourage community support, we identify potential resources for social support. Therefore, it is necessary to apply tools that allow us to carry out assessments of supportive relationships for further mobilization of the social network. Conclusion: The tools presented in this study provide a broad orientation of the tool type that best suits the needs of the professional to fulfill the demand of the elderly, allowing an appropriate choice for each situation, contributing to an integrated approach in gerontological.